Description of Anesthesia Maintenance Drug Therapy In General Anesthesia Patients - luthfi, Ahmad Luthfi Virgiawan Habibi; Suandika, Made; Bisma Yudha, Magenda (Global Indonesia Health Care (GOICARE), 2025)
Background: The purpose of general anesthesia is analgesia, eliminating anxiety, amnesia, and loss of consciousness, and suppressing cardiovascular, motor, and hormonal responses to surgical stimulation. Administering sedative and analgesic drugs is an important component in treating all critical patients. Sedatives and analgesics are used for pain management, helping to relieve patient anxiety and discomfort during invasive diagnostic and therapeutic procedures. The main indications for the use of sedatives and analgesics are to treat pain, anxiety, and agitation, amnesia, help in adjusting breathing with mechanical ventilation, and overcome decreased cellular metabolism in patients. The choice of anesthetic drug should be based on patient characteristics and conditions related to surgery and costs. The patient's condition must be really good to receive anesthesia, therefore, to avoid undesirable effects from administering anesthetic drugs, the choice of anesthetic drugs should be based on patient characteristics and conditions related to surgery and costs. During surgery, patients receive various anesthetics as maintenance anesthesia. Purpose: To understand the description of anesthesia maintenance drug therapy in general anesthesia patients at RSI Purwokerto. Method: This research is descriptive quantitative research with a cross-sectional approach. The sample used in this study was 92 general anesthesia patients at RSI Purwokerto. The sampling technique in this research used purposive sampling. Research Results: The anesthesia maintenance drug used at RSI Purwokerto was Sevoflurane as much as 80 (87%), and midazolam was used as much as 2 (2.2%). Conclusion: Most of the anesthesia maintenance drugs given to patients at RSI Purwokerto are sevoflurane.